Accurate assessment of coronary blood flow by continuous thermodilution technique: Validation in a swine model. Issue 3 (3rd June 2021) - Adjedj, Julien; Picard, Fabien; Mogi, Satoshi; Bize, Alain; Sambin, Lucien; Muller, Olivier; Varenne, Olivier; De Bruyne, Bernard; Ghaleh, Bijan
Abstract: Objective: To assess the accuracy of coronary thermodilution measurements made with the RayFlow® infusion catheter. Background: Measurements of absolute coronary blood flow (ABF) and absolute microvascular resistance (R μ ) by continuous coronary thermodilution can be obtained in humans but their accuracy using a novel dedicated infusion catheter has not yet been validated. We compared ABF values obtained at different infusion rates to coronary blood flow (CBF) values obtained using flow probes, in swine. Methods: Twelve domestic swine were instrumented with coronary flow probes placed around the left anterior descending and circumflex coronary arteries. ABF was assessed with the RayFlow® infusion catheter during continuous saline infusion at fixed rates of 5 ( n = 14), 10 ( n = 15), 15 ( n = 19), and 20 ( n = 12) ml/min. Results: In the 60 measurements, ABF measured using thermodilution averaged 41 ± 17 ml/min (range from 17 to 90) and CBF values obtained with the coronary flow probes averaged 37 ± 18 ml/min (range from 8 to 87). The corresponding R μ values were 1532 ± 791 (range from 323 to 5103) and 1903 ± 1162 (range from 287 to 6000) Woods units using thermodilution and coronary flow probe assessments, respectively. ABF and R μ values measured using thermodilution were significantly correlated with the corresponding measurements obtained using coronary flow probes (R = 0.84 [0.73–0.95] and R = 0.80 [0.69–0.88], respectively). Conclusions: ABF and R μ assessed by continuous saline infusion through a RayFlow® catheter closely correlate with measurements obtained with the gold standard coronary flow probes in a swine model.